(untitled) (Journal of the College of Basic Education, 2022)
To keep pace with the times and take up the developments in technology as a result of the informational development in the world around us. The need arose to use the Internet and direct it to serve higher education and to make curricula and programs The educational approach in Iraqi universities is not characterized by the international formula and is still within the local framework. The research is to shed light on the impact of using this technology in education and activating it as an educational method to enable